Parameters for determining the hardness and pleasantness of pomegranates (Punica granatum L.) - Melgarejo P.; Sánchez M.; Hernández F.; Martínez J.J.; Amorós A. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The quality of pomegranate seeds (the edible portion of the fruits) depends on certain parameters: basically colour, size, SS per A ratio, palatability and hardness. We have studied the hardness, pleasantness and palatability of the seeds. These are determining characteristics, as the seeds of some varieties are so hard as to be inedible, making the fruit unsuitable for fresh consumption. The study was carried out in 1996 and 1997. The difficulty in chewing the seeds was determined by two procedures: (i) measuring total fibre content; and (ii) measuring hardness (using a panel of tasters). The palatability was determined by the index of woody portion in the seeds. The results permit the pomegranate varieties analysed to be classified into hard seed (inedible) and soft seed (easily chewed). We observe a relationship between the total fibre and hardness. Palatability must be considered as a secondary index for measuring seed hardness compared with total fibre and chewing difficulty.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)